Phyllochron and differential growth between plants of french tarragon (artemisia dracunculus l.) with different source of propagation (2011)
French tarragon is included within the brochure of herbs that Colombia is offering to export. Although renewal is recommended every three or four years, in Colombia there are crops more than eight years of age and with low yield because its traditional vegetative propagation is difficult, therefore it is necessary to establish alternative propagation methods to improve its yield. In order to analyze the phyllochron and growth between French tarragon plants with different origin of propagation (micropropagation and traditional propagation), parameters to simulate field behavior from a model was estimated. From cardinal temperatures, a quadratic function of tarragon’s phyllocron, whose rate was higher in plants from micropropagation during establishment, was determined. The general meristematic activity in plants of in vitro treatment shown to be greater than plants of field treatment, as well as leaf area index (LAI), fraction of intercepted light (FLINT) extinction coefficient (K) and radiation use efficiency (RUE), which involved differences in the architecture of plants in both treatments. Distribution of biomass to leaves and stems was similar in both treatments. This is the first study using a deterministic model to analyze the effect of micropropagation in field tarragon’s growth.